Use of the multifunctional guide to gain predictability in an immediate inferior loading protocol on implants - Pulino, Bianca de Fatima Borim (2021)
The treatment with dental implants has evolved significantly from the 1970s to the present day, both in terms of planning and in bioengineering and surface treatment of these implants, with the aim of making the treatment more effective. Currently the use of immediate implants has been increasingly studied by researchers and used for the oral rehabilitation of patients. The literature shows us that the immediate insertion of post-extraction dental implants is a type of treatment with high success rates, enabling the patient to undergo only one surgery, and return to a faster masticatory and aesthetic function. This requires correct planning and adequate patient selection for successful treatment, considering bone and periodontal conditions. The aim of this study is to discuss the planning of the oral rehabilitation of a patient who underwent total extraction of the lower teeth, installation of 4 immediate dental implants and fabrication of a protocol-type immediately loaded total prosthesis.